2016
DOI: 10.16986/huje.2016015182
|View full text |Cite
|
Sign up to set email alerts
|

Açık Uçlu Sorularla Yapılan Ölçmelerde Klasik Test Kuramı ve Çok Yüzeyli Rasch Modeline Göre Hesaplanan Yetenek Kestirimlerinin Karşılaştırılması

Abstract: ÖZ:Bu araştırmada, açık uçlu sorularla yapılan ölçmelerde klasik test kuramı (KTK) ve çok yüzeyli Rasch modeline (ÇYRM) göre hesaplanan yetenek kestirimlerinin karşılaştırılması amaçlanmıştır. Araştırma sekizinci sınıfa devam eden 100 öğrenci ile çalışmada puanlayıcı olarak görev alan dört matematik öğretmeninin katılımıyla gerçekleşmiştir. Çalışmanın verileri, açık uçlu altı matematik sorusundan oluşan bir başarı testi ve bu soruların puanlanmasında kullanılan bütüncül bir rubrik yardımıyla toplanmıştır. Açık… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
1
8
0
6
Order By: Relevance
“…The prepared rubric has been test on students' written answers and founded functional. It was also found that the prepared rubric was compatible with the studies in the literature on the evaluation of open-ended questions such as İlhan [19], Doğan [21], Piffer [31], and Mozaffari [34].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The prepared rubric has been test on students' written answers and founded functional. It was also found that the prepared rubric was compatible with the studies in the literature on the evaluation of open-ended questions such as İlhan [19], Doğan [21], Piffer [31], and Mozaffari [34].…”
Section: Discussionsupporting
confidence: 73%
“…Open-ended questions which commonly used in education contribute to the development of skills such as problem solving, creative thinking, reasoning, generalization, and decision making [19,20]. On the other hand, open-ended questions have their own limitations such as ensuring the reliability of the scorer and establishing objective evaluation criteria [21].…”
Section: Introductionmentioning
confidence: 99%
“…Değerlendirme formunda yer alan "3" düzeyinin (bilgi var ve gerekli şekilde açıklanmış) ise en çok kullanılan düzey olduğu belirlenmiştir. Düzeylerin işlevini yerine getirdiğinin söylenebilmesi için puanlama düzeylerindeki dağılımın dengeli olması ve her düzeyde en az 10 katılımcının bulunmuş olması ve uyum-dışı istatistiklerinin de 0.5 ile 1.5 aralığında değerler almış olması beklenir (İlhan, 2016;Linacre, 2014). Buna göre, düzeylere ilişkin frekans değerleri incelendiğinde tüm düzeyler için istenilen değerlere ulaşılabildiği ve uyum-dışı istatistiklerinin de istenilen aralıkta yer aldığı gözlenmektedir.…”
Section: ____________________________________________________________unclassified
“…Therefore, the abilities of individuals can be estimated more accurately. When the literature is reviewed and item and ability parameters obtained from CTT and IRT are compared, there are studies analyzing parameter invariance (Akyıldız & Şahin, 2017;Bulut, 2018;Çakıcı-Eser, 2013;Cappelleri, Jason Lundy, & Hays, 2014;Çelen & Aybek, 2013;İlhan, 2016;Macdonald & Paunonen, 2002;Stage, 1998aStage, , 1998bXu & Stone, 2012). In these studies, generally parameters obtained from IRT and CTT are compared and invariance property is generally obtained in IRT.…”
Section: Introductionmentioning
confidence: 99%